Security and a Financial Theory of Investment - Gordon, Myron J. (Quarterly Journal of Economics, 1960)
Introduction, 472. — Origin of the theory, 474. — Definition of risk, 476. — The investment model, 479. — Two theoretical objections to the theory, 481. — Evidence on the theory, 483. — Examination of sample data, 486. — Further research, 490.